(untitled) (REMUNOM, 2025)
Endometriosis is a chronic gynecological disease characterized by the presence of endometrial tissue outside the uterus, affecting approximately 10% of women of reproductive age. This condition can lead to severe pain, infertility, and significant impairment of quality of life, in addition to impacting patients’ physical, emotional, and social aspects. According to Santos et al. (2020), endometriosis is associated with debilitating symptoms, such as severe dysmenorrhea, chronic pelvic pain, dyspareunia, and bowel or urinary changes, which often result in limitations in daily life and absenteeism from work. The diagnosis of endometriosis still faces challenges, including the lack of noninvasive diagnostic methods and the long interval between the onset of symptoms and clinical confirmation, which can last up to seven years. Regarding therapeutic approaches, options include pharmacological treatment, such as the use of hormonal contraceptives and GnRH agonists, and surgical surgeries, indicated in more severe cases. Recent studies also highlight integrative therapies, such as physiotherapy, lifestyle changes and psychological support, which have proven effective in improving patients’ quality of life (Oliveira; Ferreira, 2021). Based on this information, this work is structured as a bibliographic review, addressing the gathering, analysis and systematization of information from relevant studies in the scientific literature on the subject. This review encompasses the multiple impacts of endometriosis on women’s lives, analyzing the available therapeutic strategies and advances in the management of the disease. The relevance of the topic is the growing recognition of endometriosis as a public health condition, requiring greater awareness, training of professionals and policies that ensure early diagnosis and adequate treatment. Promoting a multidisciplinary and personalized approach is essential to reduce patients’ suffering, improve prognosis and provide a healthier and more productive life.